3-[4-(Trifluoromethyl)phenyl]propanoic acid - Guan, Jian-Ning (International Union of Crystallography, 2009)
In crystal of the the title compound, C(10)H(9)F(3)O(2), inversion dimers linked by pairs of O—H⋯O hydrogen bonds occur.